2003
DOI: 10.1046/j.1365-2591.2003.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue reaction initiated by different sealers

Abstract: This study suggests that sealers with different chemical compositions initiate different histological reactions. It also emphasizes the importance of confining root filling to the canal system because all sealers initiate inflammatory reactions when they are present in the apical tissues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 23 publications
4
74
1
6
Order By: Relevance
“…Although sealers should be confined within the root canal, their inadvertent extrusion beyond the apical foramen into the periradicular tissues may occur 3) . Thus toxic components of sealers, particularly in cases of open apex due to iatrogenic over-instrumentation, pathologic root resorption, or non-vital teeth with immature roots, would damage both the periodontal ligament and alveolar bone 4) , adversely affecting the treatment outcome. Therefore, sealers should have good biocompatibility and should be well tolerated by the periradicular tissues 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Although sealers should be confined within the root canal, their inadvertent extrusion beyond the apical foramen into the periradicular tissues may occur 3) . Thus toxic components of sealers, particularly in cases of open apex due to iatrogenic over-instrumentation, pathologic root resorption, or non-vital teeth with immature roots, would damage both the periodontal ligament and alveolar bone 4) , adversely affecting the treatment outcome. Therefore, sealers should have good biocompatibility and should be well tolerated by the periradicular tissues 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Average thickness of the fibrous capsules of each specimen was evaluated in 10 separate areas. Fibrous capsules were considered to be thin when thickness was <150 μm and thick at >150 μm 11,13) . Evaluation of new bone formation around the implanted materials was carried out as follows: Grade 0, no bone formation; Grade I, Slight, presence of bony islets and coverage of less than 25% of the material surface with bone; Grade II, Moderate, coverage of at least 50% of the material surface with bone; Grade III, Extensive, complete coverage of the material surface with bone or the formation of an osseous bridge around the material 14) .…”
Section: Evaluation Parametersmentioning
confidence: 99%
“…Unfortunately, several studies have shown that most commercially available materials can cause mild to severe inflammatory changes in apical tissues, leading to bone destruction [21][22][23][24]. Endodontic sealants may also affect periradiculare tissues by direct contact in cases of overfilling or extracted components.…”
Section: Discussionmentioning
confidence: 99%
“…Endodontic sealants may also affect periradiculare tissues by direct contact in cases of overfilling or extracted components. They can be released into the surrounding tissues by the dentin tube and channels from the apical level [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%